Eva, Kopi and Matcha - Evangeline Neo (MPH Group Publishing Sdn Bhd, 2015)
Who would have thought that Eva's crossover from one red dot to another could be peppered with so many good laughs? Eva, Kopi and Matcha is a light-hearted and witty narration of cultural differences in Singapore and Japan, matter-of-factly spewed out by Eva, a typical Singaporean with an “auntie” mindset. In this humorous trajectory of everyday musings, Eva takes a funny, and often self-deprecating look at random and awkward mismatches between the two red dots, revealing much exasperation and delight along the way. Together with Kopi and Matcha, her imaginary pets, Eva tries to suss out a life in Japan and find a place in her home away from home.